Accurate assessment of nonalcoholic fatty liver disease lesions in liver allograft biopsies by a smartphone platform: A proof of concept. Issue 9 (1st July 2020) - Cesaretti, Manuela; Gal, Jocelyn; Bouveyron, Charles; Diaspro, Alberto; Fontas, Eric; Antonini, Andrea; Anty, Rodolphe; Iannelli, Antonio; Patouraux, Stephanie
Abstract: Macrovesicular steatosis (MS) is a major risk factor for liver graft failure after transplantation and pathological microscopic examination of a frozen tissue section remains the gold standard for its assessment. However, the latter requires an experienced in‐house pathologist for correct and rapid diagnosis as well as specific equipment that is not always available. Smartphones, which are must‐have tools for everyone, are very suitable for incorporation into promising technology to generate moveable diagnostic tools as for telepathology. The study aims to compare the microscopic assessment of nonalcoholic fatty liver disease (NAFLD) spectrum in liver allograft biopsies by a smartphone microscopy platform (DIPLE device) to standard light microscopy. Forty‐two liver graft biopsies were evaluated in transmitted light, using an iPhone X and the microscopy platform. A significant correlation was reported between the two different approaches for graft MS assessment (Spearman's correlation coefficient: r = .93; p < .001) and for steatohepatitis feature ( r = .56; p < .001; r = .45; p < .001). Based on these findings, a smartphone integrated with a cheap microscopy platform can achieve adequate accuracy in the assessment of NAFLD in liver graft and could be used as an alternative to standard light microscopy when the latter is unavailable. Abstract : The reference method for liver graft quality assessment is the pathological examination of a biopsy. However, it requires the availability of microscopy, cryostat facility, and an expert pathologist 24 hr a day that it may result impossible for all donor hospitals. Low‐cost microscopical platform could transform a smartphone into a portable microscope available for liver graft assessment in organ procurement setting. The performance of the DIPLE device was compared to white‐light microscopy. A significant correlation was found between the two different approaches for macrosteatosis graft assessment ( r = .93; p < .001) and for steatohepatitis features ( r = .56; p < .001; r = .45; p < .001). No significant correlation for microvacuolar hepatic steatosis evaluation was found comparing the two approaches ( r = .41; p = .006). The advantage of data capability, internet connectivity of the smartphone and the robustness of the DIPLE device, would be particularly useful in remote organ procurement settings for pathological specimens' examination.